The Effects of Bromocriptine on Preventing Postpartum Flare in Systemic Lupus Erythematosus Patients from South China - Qiu Qian; Liang Liuqin; Li Hao; Yuan Shiwen; Zhan Zhongping; Chen Dongying; Lian Fan; Xu Hanshi; Yang Xiuyan; Ye Yujin (Journal of Immunology Research)
Objective. Prolactin plays an important role on the disease flare of postpartum SLE patients. 76 pregnant SLE patients were enrolled in this study to evaluate the efficacy of bromocriptine (an inhibitor of prolactin secretion) on preventing the postpartum disease relapse. Methods. Patients were randomly divided into the treatment group (bromocriptine, 2.5 mg oral, twice a day for 14 days after delivery) and the control group. All the patients were followed up for 12 months. Clinical features were recorded every 4 weeks. Serum prolactin and estradiol levels were measured at the second week and the second month after delivery. The endpoint of the study was disease relapse and defined when SLEDAI score increased by ≥3 points from the antenatal baseline. Results. (1) Serum levels of prolactin and estradiol decreased significantly in bromocriptine treatment group at the second week (P<0.001) and second month (P<0.05) after delivery compared to control group. (2) The relapse rate of the treatment group was lower than the control group (χ2=4.68, P=0.0305). Conclusions. Two weeks of oral bromocriptine treatment in postpartum SLE patients may relieve the disease from hyperprolactinemia and hyperestrogenemia and may be beneficial in preventing the patients from disease relapse.